2016
DOI: 10.1016/j.fuel.2016.08.080
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of surface deposition in a simulated fuel injector feed arm with sudden expansion/contraction

Abstract: Article:Alborzi, E., Blakey, S., Ghadbeigi, H. orcid.org/0000-0001-6507-2353 et al. (2 more authors) (2016) Investigation of surface deposition in a simulated fuel injector feed arm with sudden expansion/contraction. Fuel, 186. pp. 534-543. ISSN 0016-2361 https://doi.org/10.1016/j.fuel.2016.08.080Article available under the terms of the CC-BY-NC-ND licence (https://creativecommons.org/licenses/by-nc-nd/4.0/) eprints@whiterose.ac.uk https://eprints.whiterose.ac.uk/ Reuse Unless indicated otherwise, fulltext … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The nonlinear temperature rise along the external surface of a simulated burner feed arm under engine representative condition is reported in refs. 40,39 By virtue of mounting a pyrometer on an automated positioning bed, the temperature in the localized areas can be captured as discrete measurement points, along a small section of the capillary, and used to create a time-profile of temperature rise along the wall. The main advantage of the HiReTS method is the ability to quantify the thermal stability of fuel using relative measures such as HiReTS number.…”
Section: ■ Experimental Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The nonlinear temperature rise along the external surface of a simulated burner feed arm under engine representative condition is reported in refs. 40,39 By virtue of mounting a pyrometer on an automated positioning bed, the temperature in the localized areas can be captured as discrete measurement points, along a small section of the capillary, and used to create a time-profile of temperature rise along the wall. The main advantage of the HiReTS method is the ability to quantify the thermal stability of fuel using relative measures such as HiReTS number.…”
Section: ■ Experimental Workmentioning
confidence: 99%
“…Our previous findings show that the profile of temperature rise along a heated tube in an aeroengine representative condition is nonlinear and fuel-specific. The nonlinear temperature rise along the external surface of a simulated burner feed arm under engine representative condition is reported in refs. , …”
Section: Experimental Workmentioning
confidence: 99%
“…The molecules are disassociated according to two different axis to increase the post-processing selectivity. Although this method is rare compared to one-dimensional chromatography, it is now used in research ( [19,20,21,22,23,25,26]) and in industry (standard ASTM UOP990-11 [24]). Jennerwein et al showed this test method to be more reliable for modern and complex fuels because of a higher sensitivity [25].…”
Section: Experimental Methodsmentioning
confidence: 99%
“…A number of studies have investigated the conductivity of typical deposits found in aviation fuel autoxidation test rigs of a range of scales. TeVelde and Glickstien [23] reported a strong variation in deposit conductivity with deposit thickness between 20 µm and 25 µm varying by an order of magnitude from 0.017W/m 2 K to 0.17W/m 2 K. Earlier experimental work on sectioned tubes from the AFT-STU [4] has suggested an estimated thermal conductivity of to 0.012W/m 2 K would be appropriate and was validated against microscope assessment of sectioned tubes from the rig. This agrees well with the work of Tevelde and Glickstein as the deposit was below 20 µm for the majority of the testing work.…”
Section: Model Validationmentioning
confidence: 95%